Parental knowledge, attitude and practice of oral hygiene of special children in Bangalore - Anagha Saseendran; Priya Nagar; K S Nameeda; K Fathimath Nihala (SRM Journal of Research in Dental Sciences, 2021)
Background: Oral hygiene of special children is directly related to their disability, and parents play a key role in a child's oral hygiene maintenance which would influence their general health condition. Aim: The aim of this study was to evaluate the knowledge and attitude of parents of special children toward oral hygiene maintenance and to correlate the same with educational and socioeconomic status. Materials and Methods: A cross-sectional study was conducted among the mothers of children from special schools in Bangalore. The survey included questions related to knowledge and attitude of parents and practice of oral hygiene maintenance for their children. The results were tabulated and subjected to statistical analysis using Chi-square test. P < 0.05 was considered to be statistically significant. Results: The parents of the special children had sufficient knowledge on the maintenance of oral hygiene, and the educational status of the parent had a positive impact on the child's oral health. Conclusion: Oral hygiene maintenance of special children is extremely important as primary teeth serve as the milestone in orofacial growth and development.